IMPROVING THE STUDENTS' READING COMPREHENSION OF ANALYTICAL EXPOSITION TEXT BY USING THINK-PAIR-SHARE (TPS) - Azizah, Nur; Hayati, Resti; Fadloeli, Odo (IKIP Siliwangi, 2019)
This study aims to improve reading comprehension for the eleventh-grade students at SMA MATHLAUL ANWAR, consisting of 30 students in using the think-pair-share model. The researchers applied the think-pair-share model because this considered the model as one of the best teaching methods for teaching. Students use the think-pair-share model in learning activities to raise their reading comprehension, increase their enthusiasm, and become active in classroom learning. Besides, the benefits of using the Think-Pair-Share method in reading discussions will reveal opportunities to encourage students to be active in the learning process, such as discussing and helping each other solve problems or assignments. That will have a positive impact on students in accepted learning material provided by the teacher. In this study, the writer researched three cycles to achieve student improvement in reading comprehension. The results of the tests that have been done lead to the mean grade of students in each cycle as a follow-up pre-cycle is 68, while in the second cycle 71, and the last can be seen as a terrace in the third cycle 75. Based on the mean grade of two cycles above, we can prove that the think-pair-share technique has succeeded in increasing the students' ability to teach reading comprehension in analytical exposition texts.